Stabilisasi Kapur Terhadap Kuat Dukung Tanah Lempung Dengan Variasi Diameter Butiran Tanah - MURHANDANI, ULUL WAHYU, Qunik Wiqoyah, S.T., M.T, Anto Budi L., S.T., Msc (2015)
According Wiqoyah (2003) Tanon soil is clay with a percentage of 94.13% through sieve No. 200, liquid limit (LL) = 88.03%, the plasticity index (IP) = 49, 44%. Based on the methods of the American Association Of State Highway And Transportation Officials (AASHTO), clay Tanon included in the group A-7-5 and classification Unified Soil Classification System (USCS) belong to the group CH ie inorganic clay with high plasticity. Based on the research above example that stabilization with lime can improve soil conditions. Therefore in this study is done with a variety of soil granules through sieve No. 4, through sieve No. 30 and sieve No. 200, to determine whether the size of a grain of soil affect the physical and mechanical properties of the clay soil. Testing was conducted on the physical properties of the soil mixture and CBR test with the addition of lime amounted to 2.5% and 5%. Results of testing the physical properties of the soil mixture obtained water content, density (specific gravity), the liquid limit and plasticity index fell, while the value of plastic limit and shrinkage limit rose. Mix soil classification according to AASHTO system, including a group of A-7-5, while according to the USCS system, clays (pass the No. 4, No. 30 and No. 200) + 2.5% lime into the group CH and clay ( pass the No. 4, No. 30 and No. 200) + lime 5% belong to the group of MH. The test results of mechanical properties, of Proctor standard test showed a decrease in weight of dry volume and the largest decline occurred in the land passes No. 200 + lime 5% by volume dry weight values of 0.980 g / cm3, for optimum water content largest increase occurred in soil sieve No. 4 at the limestone addition of 5% with the results of the optimum water content of 32.46%. CBR test results have increased, largest increase occurred in soil sieve No. 4 to 5% with the addition of lime soaked CBR result of 6.311%. Unsoaked CBR value also increased, from CBR value of land unsoaked sieve No. 4 + lime 2.5% at 21.778% to 24.556% by the addition of lime 5%. Keywords: clay, stabilization, lime, physical properties, strong support.